Korean dramas as media to increase daily speaking skills in Higher Education - Feby Dita Pujianti; Tazkiya Weningdrya (Inovasi Kurikulum, 2023)
This research adopts a quantitative approach to investigate the effect of watching Korean dramas on the use of words and speaking style in the daily lives of university students. A total of 27 respondents were selected as the sample for this study. Data were collected through a questionnaire that included questions about the students' habits of watching Korean dramas, the influence on their word usage and speaking style, as well as their motivation to further study the Korean language and culture after watching the dramas. The findings indicate that the respondents showed a high level of interest in Korean dramas, with a majority using Netflix as their primary platform for watching. On average, the respondents spent 1-4 hours per day watching Korean dramas. The research also revealed that Korean dramas had a positive contribution to enriching the respondents' vocabulary and speaking style. Although not all respondents mastered a large number of words from watching Korean dramas, some of them were able to develop a considerable command of the Korean language. Additionally, a small percentage of respondents successfully adopted the speaking style and language from the dramas. AbstrakPenelitian ini menggunakan pendekatan kuantitatif untuk menginvestigasi pengaruh menonton drama Korea terhadap penggunaan kata dan gaya berbicara dalam kehidupan sehari-hari mahasiswa. Sebanyak 27 responden dari kalangan mahasiswa diambil sebagai sampel dalam penelitian ini. Data dikumpulkan melalui kuesioner yang berisi pertanyaan tentang kebiasaan menonton drama Korea, pengaruhnya terhadap penggunaan kata dan gaya berbicara, serta motivasi mahasiswa untuk mempelajari lebih lanjut bahasa dan budaya Korea setelah menonton drama. Hasil penelitian menunjukkan bahwa sebagian besar responden menunjukkan minat yang tinggi terhadap drama Korea dan mayoritas menggunakan aplikasi Netflix sebagai media utama untuk menontonnya. Rata-rata, responden menonton drama Korea selama 1-4 jam setiap harinya. Penelitian ini juga mengungkapkan bahwa drama Korea memberikan kontribusi positif dalam memperkaya kosakata dan gaya berbicara mahasiswa. Meskipun tidak semua responden menguasai banyak kata-kata dari menonton drama Korea, namun masih ada sebagian responden yang mampu mengembangkan penguasaan bahasa Korea dalam jumlah yang lumayan banyak. Selain itu, sebagian kecil responden berhasil mengadopsi gaya bicara dan bahasa Korea setelah menonton drama tersebut.Kata Kunci: Drama Korea; kemampuan berbahasa; Korean wave; media pembelajaran